Новые слепняки (Heteroptera, Miridae) фауны Туркменской ССР - Пучков, В.Г. (Вестник зоологии, 1974)
﻿The monotypical genera are described: Bobocris gen. n. with type-species B. roseolus sp. n., Monocris gen. n. with type-species M. griseus sp. n., Lopidodenus gen. n. with type-species L. ogivus sp. n. and Macrotylus hymenocratii sp. n.